Cosmological information from quasar-galaxy correlations induced by weak lensing - Ménard, Brice; Bartelmann, Matthias (Astronomy and astrophysics, 2002)
Astronomy & Astrophysics (A&A) is an international journal which publishes papers on all aspects of astronomy and astrophysics